ANALISIS PENYEBAB ARTEFAK PADA HASIL RADIOGRAF MENGGUNAKAN COMPUTED RADIOGRAPHY (CR) - Hasmi, Nur; Pathuddin, Herlina (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2022)
CR is a device capable of producing high quality radiographic images compared to conventional ones. Even though it is capable of producing high image quality, there are still artifacts in radiographic images. These artifacts can lead to misdiagnosis of the disease. Artifacts represent images that should not be present in radiographs. The purpose of this study was to determine the cause of the artifacts on the radiograph using the CR system. This study used a literature study method by analyzing journals related to the causes of artifacts in the radiographic images using the CR system. Based on the results of a literature review, it can be concluded that the factors causing artifacts are due to operator error, tool error, and artifacts that arise due to foreign objects.